2007
DOI: 10.1002/art.22952
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a fusion protein between thermally responsive elastin‐like polypeptide and interleukin‐1 receptor antagonist: Sustained release of a local antiinflammatory therapeutic

Abstract: Objective. Interleukin-1 receptor antagonist (IL1Ra) has been evaluated for the intraarticular treatment of osteoarthritis. Such administration of proteins may have limited utility because of their rapid clearance and short half-life in the joint. The fusion of a drug to elastin-like polypeptides (ELPs) promotes the formation of aggregating particles that form a "drug depot" at physiologic temperatures, a phenomenon intended to prolong the presence of the drug. The purpose of this study was to develop an injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 42 publications
3
112
0
Order By: Relevance
“…This approach maintained both phase transition behavior as well as activity for the drug domain, consistent with results for other ELP-drug conjugates. [32,33] Advantages of this system include acceptable expression levels of chimeric proteins with high drug-to-carrier ratios compared with chemical conjugation. [48][49][50] Purification of genetically engineered ELPs generates proteins of high purity and low endotoxin levels that have been demonstrated to be non-immunogenic, non-pyrogenic, and biocompatible, with endogenous amino acid degradation products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach maintained both phase transition behavior as well as activity for the drug domain, consistent with results for other ELP-drug conjugates. [32,33] Advantages of this system include acceptable expression levels of chimeric proteins with high drug-to-carrier ratios compared with chemical conjugation. [48][49][50] Purification of genetically engineered ELPs generates proteins of high purity and low endotoxin levels that have been demonstrated to be non-immunogenic, non-pyrogenic, and biocompatible, with endogenous amino acid degradation products.…”
Section: Discussionmentioning
confidence: 99%
“…The higher fusion protein K D and IC 50 compared against commercial sTNFRII is a trend for other fusion proteins. [33,53] The necessary K D or IC 50 required for this protein to achieve efficacy in the drug delivery concept proposed here depends also on other features of the in vivo system, such as clearance time and mechanism from the targeted space, total amount of protein delivered, and resolubilization kinetics. Caution is important in directly comparing against the commercial sTNFRII because the gene sequence and technique for synthesis and purification are quite different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Betre et al, an aggregating ELP was shown to have a 25-fold longer half-life in the injected joint than an equivalent molecular weight protein that remains soluble and does not aggregate [165]. In an accompanying study by Shamji et al, an ELP-IL1Ra fusion displayed a complete recovery of IL1Ra activity, matching that of the commercial antagonist [166]. They also demonstrated the facile collagenase degradation of the ELP domain, which may further promote the therapeutic efficacy of this drug delivery system.…”
Section: Peptide-elp Fusion Proteinsmentioning
confidence: 97%
“…3,4 Tropoelastin is the precursor to elastin, a key component of elastic skin fibers. Previous skin remodeling studies have suggested that elastin could be useful in dermal regeneration.…”
mentioning
confidence: 99%